2020
DOI: 10.1177/2325967120952315
|View full text |Cite
|
Sign up to set email alerts
|

The Loop ’n’ Tack Knot: Biomechanical Analysis of a Novel Suture Technique for Proximal Biceps Tenodesis

Abstract: Background: Secure tendon grasping is critical to the success of any tenodesis procedure. Several techniques currently used for tendon grasping can result in longitudinal splitting of the tendon, causing construct failure and failure of the tenodesis. Purpose: To compare the Loop ’n’ Tack knot as a tendon-grasping technique with other common suture techniques. We investigated the biomechanical strength and mode of failure. Study Design: Controlled laboratory study. Methods: Eleven matched pairs of proximal bic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…A kind of all-arthroscopic tenodesisdthe loop 'n' tack techniquedwas first reported by Duerr et al 10 using a FiberSnare. Later, Acosta et al 12 conducted an in vitro biomechanical study and found that the loop 'n' tack method had an ultimate load to failure similar to that of the Krackow stitch. Therefore, the loop 'n' tack technique has proved safe and effective.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A kind of all-arthroscopic tenodesisdthe loop 'n' tack techniquedwas first reported by Duerr et al 10 using a FiberSnare. Later, Acosta et al 12 conducted an in vitro biomechanical study and found that the loop 'n' tack method had an ultimate load to failure similar to that of the Krackow stitch. Therefore, the loop 'n' tack technique has proved safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…Duerr et al 10 first proposed the "loop 'n' tack knot" biceps tenodesis technique, applied in all-arthroscopic LHBT tenodesis, with satisfactory clinical outcomes. 11 However, this simple technique required specialty sutures, FiberSnare or FiberLink (Arthrex, Naples, FL), 10,12 which were commercially unavailable in many regions and limited the further promotion of this technique. Therefore, in this article, we propose a suture techniquedthe lark-loop techniquedthat resembles the configuration of the lark's head knot, based on an alteration of the loop 'n' tack technique.…”
mentioning
confidence: 99%
“…Acosta and others used the three-dimensional image analysis method to analyze the kinematic characteristics of Chinese professional football players throwing long-distance out of bounds, and came to the conclusion that they want to throw long-distance and high-quality out of bounds. Athletes need to mobilize their body muscles as much as possible for orderly swing from bottom to top, and can release the ball within a reasonable and effective angle range [7]. Lee and others used six optical cameras to obtain the lower limb technical action images of 10 men's volleyball players during the take-off period of front and rear buckle.…”
Section: Literature Reviewmentioning
confidence: 99%
“…14 Although the classic Krackow suture technique shows superior biomechanical properties for biceps tendon fixation, it is not easy to complete under arthroscopy. 15 Therefore, secure tendon grasping ability of the suture techniques is critical for successful arthroscopic tenodesis in order to obtain a lower incidence of Popeye deformity of the upper arm with endoscopic fixation. The Lark-Loop stitch, newly presented in 2022 by Zhou et al 16 constructs a Lark's head knot, holding tendon tissue with the two suture ends piercing through the middle portion of the tendon.…”
Section: Introductionmentioning
confidence: 99%